Prevalence of Post-Traumatic Stress Disorder among Adolescents in Mosul City after War - Khaleel, Rayyan I.; Al-Doori, Nuhad M. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: Post Traumatic Stress Disorder (PTSD) among adolescents is increasing worldwide especially in violent conflicts and war zones. Iraq is consistently exposed to large-scale traumatic events such as successive wars, economic sanction, sustainable organized violence, and terrorism. This unsafe situation has negative impacts on the psychosocial status of the whole Iraqi community, particularly children and adolescents.Objectives: To assess the prevalence of posttraumatic stress disorder among adolescents in Mosul city, and to figure out the association between PTSD with certain socio-demographic characteristics..Method: The current study was based on a cross sectional design, which conducted on a sample consisted of 1034 adolescents aged 15 to 21 years old age was randomly selected from 13th schools in the Mosul city. Participants were interviewed by self-administrated questionnaire include sociodemographic characteristics and Post traumatic stress disorder according to DSM-IV scale.Results: The study resulted that 44.7% of the participants were aged between (17 - 18) years old, 52.5% of the participants were male. The study showed that 10.4% of adolescents reported mild PTSD, 44.3% showed moderate, 40.5% revealed severe PTSD while 4.6% of adolescents suffering from very severe PTSD and girls reported more PTSD than boys. The results showed a significant association between the PTSD with age of adolescents and family monthly income.Conclusions: The unsafe situation in Iraq has led to high trauma exposure and a high prevalence rate of PTSD among adolescents in Mosul city. It was more prevalent among 19-21years age group and was more prevalent among females than males. The study explored a number of factors that are associated with this increased rate. The urgent need to develop adolescents’ health care services in Iraq must be supported. There may be an even greater need for school-based programs to promote child and adolescent health and well-being, particularly as Iraqi children and adolescents continue to be exposed to violence, and the most distressing lifetime traumas.